2021
DOI: 10.1016/j.cellimm.2021.104425
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-11 regulates lung inflammation in response to house dust mites

Abstract: Asthma is an in ammatory lung disorder characterized by mucus hypersecretion, cellular in ltration, and bronchial hyper-responsiveness. House dust mites (HDM) are the most prevalent cause of allergic sensitization. Canonical and noncanonical in ammasomes are multiprotein complexes that assemble in response to pathogen or danger-associated molecular patterns (PAMPs or DAMPs). Murine caspase-11 engages the noncanonical in ammasome. We addressed the role of caspase-11 in mediating host responses to HDM and subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 114 publications
0
2
0
Order By: Relevance
“…HDM is a common indoor aeroallergen associated with the development of asthma [ 14 ] that can induce CLI and lung epithelial damage [ 14 17 ]. Thus, we hypothesized that chronic exposure to HDM could accelerate LC development in susceptible hosts through the induction of pro-inflammatory cytokines such as IL-1β [ 18 20 ]. At the cellular level, IL-1β is known to stimulate angiogenesis in the tumor microenvironment (TME) [ 21 ], and to induce the production of IL-6 and IL-17A, which are well-established mediators of tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…HDM is a common indoor aeroallergen associated with the development of asthma [ 14 ] that can induce CLI and lung epithelial damage [ 14 17 ]. Thus, we hypothesized that chronic exposure to HDM could accelerate LC development in susceptible hosts through the induction of pro-inflammatory cytokines such as IL-1β [ 18 20 ]. At the cellular level, IL-1β is known to stimulate angiogenesis in the tumor microenvironment (TME) [ 21 ], and to induce the production of IL-6 and IL-17A, which are well-established mediators of tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…Activated caspase-1 subsequently promotes proteolytic maturation and secretion of the pro-inflammatory cytokines interleukin (IL)-1β and -18 through GSDMD pores [ 13 , 14 , 15 , 16 ]. Emerging studies have demonstrated that non-canonical inflammasomes also play critical roles in inflammatory responses and in numerous infectious and inflammatory diseases [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%